Generalization on Both Sides of a Mutualism: Pollinators of Jacquemontia curtisii in Southern Florida - Suzanne Koptur (Plants)
Jacquemontia curtisii Peter ex Hallier f. is common in the pine rocklands of the southern part of peninsular Florida, with its white star-shaped flowers open to visits from many species of arthropods. Its flowers are visited by a wide array of insects, especially Hymenoptera and Lepidoptera. To determine if any of these flower visitors are specialized to J. curtisii, we observed visitors to the flowers of this species, catching visitors and sampling the pollen from their bodies. We examined stigmas of J. curtisii from 12 different sites to see how many plant species’ pollen was found and the size of the pollen loads. Though it seemed like many insects were visiting J. curtisii exclusively when it was in bloom, a surprising number had pollen of two or more other co-occurring plant species, indicating that the flower-visiting bees were generalists, as were the flowers of Jacquemontia curtisii. We compared the list of flower visitors with those observed at two previously studied southern Florida Jacquemontia species, J. pentanthos (Jacq.) G. Don and J. reclinata House ex Small, and compared pollen/ovule ratios of the three species, making predictions about the breeding systems of J. curtisii and J. pentanthos, as their P/Os are larger than those of J. reclinata, which was shown previously to be mostly self-incompatible.